Urgensi Mempelajari Ontogeni dan Filogeni dalam Pembelajaran Biologi di SMA - Damayanti, Anggia Fitri; -, Ridwan; Hidayat, Topik (Jurusan Pendidikan Biologi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Timor, 2024)
Ontogeny is the process of individual development from embryo to adult, while phylogeny is the analysis of evolutionary relationships between species. Ontogeny and phylogeny form the basis for understanding the development of organisms and the history of evolution, as well as for further studies in biology. This research aims to analyze the urgency of studying ontogeny and phylogeny in high school biology learning. The research was conducted using a literature study method on articles and references relevant to the topic. The analysis of the literature indicates an urgency to study ontogeny and phylogeny in high school biology learning. Supported by appropriate learning approaches and models, knowledge related to ontogeny and phylogeny needs to be taught to high school students to enhance their understanding of more complex biological concepts.